An analysis of mobile internet service in Thailand: Implications for bridging digital divide - Chalita Srinuan; Pratompong Srinuan; Erik Bohlin (International Telecommunications Society (ITS), 2011)
Mobile Internet is growing around the world without exception for developing countries like Thailand by passing the poor legacy wired infrastructure. This study attempts to provide guidance to a national regulatory agency (NRA) by addressing the following question: What are the key determining factors to explain the probability that individual consumer will use mobile Internet? The discrete choice model is employed to empirically examine whether the service and application attributes, socio-economic variables and service provider has systematic link with the decision of consumer. The data from a national survey in 2010 commissioned by the National Telecommunications Commission (NTC) of Thailand is used for the analysis. Based on the findings, fixed telephony, e-mail, age, area of living and mobile operator are recognized as the strongest determinants for mobile Internet adoption. The findings suggest that the mobile Internet becomes an alternative technology to bridge the digital divide since a group of people who have no fixed Internet connection at home they can connect the Internet via mobile Internet. As such, telecom regulator and policy makers need to consider the policies regarding to infrastructure investment frequency allocation, content and application development and competition in order to stimulate the growth of mobile Internet adoption and close the digital divide within country.
Keywords: 330; Mobile Internet; digital divide; developing country